Early Intervention Orientation and Mobility: A Delphi Study of the Content of the Birth to 6 Orientation and Mobility Skills Inventory (B6OMSI). (September 2021) - Baguhn, Sarahelizabeth
Introduction: The objective of this research was to identify the appropriate content for an orientation and mobility (O&M) assessment for young children. It is necessary to have a reliable and valid assessment tool to evaluate whether young children are making adequate gains in response to early intervention efforts in O&M. Very little literature exists on the O&M needs of children aged birth to 6 years because of the roots in adult rehabilitation of the field of O&M.Methods: A group of expert-level professionals in the field of early intervention O&M engaged in a consensus process to establish face validity and content validity of the assessment items, which was accomplished using a Delphi study to identify relevant topics for assessment as a first step in developing a research-based assessment tool. Cutoffs for agreement were established prior to analysis, with 90% consensus for face and content validity of a high-stakes assessment that allows the score on the assessment to serve as a snapshot of a child's progress.Results: All skills and concepts on the assessment were validated, and seven new items were added.Discussion: The resultant assessment tool is comprehensive in measuring the areas of O&M for young children that specialists found useful for determining the need for services and monitoring progress, does not contain extraneous test questions, and can stand alone as a snapshot of student progress. One item was added to the background information portion of the assessment tool because of its usefulness to some practitioners despite a consensus level below 90%. Future research should seek to establish construct validity and reliability measures.Implications for practitioners: Orientation and mobility specialists can begin using the updated item tool with improved content validity available from the New Mexico School for the Blind website.